Implementation Of Micro, Small & Medium Enterprise (Umkm) Assistance Policy - Fakhri Fakhruroji Muhasa; M. Tegar Firmansyah; Moh. Taufik Hidayat; Sri Wulandari (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Small and medium enterprises (MSMEs) in Cirebon Regency face several challenges, such as a lack of creating new ideas, a low level of quality of human resources, many MSMEs that do not have official legality and low access to capital.  This study aims to understand the implementation process of Cirebon Regent Regulation No. 44 of 2022 which regulates Micro Business Assistance in Cirebon Regency, the research was conducted using qualitative methods through a descriptive approach to describe the phenomena that occur. Policy implementation, according to an analysis based on George Edward III's theory, is influenced by four main factors: communication, available resources, attitudes or dispositions, and bureaucratic structure. These factors determine the success or failure of the policy implementation. The results showed that the implementation of the MSME mentoring policy in the Cirebon district, the implementation was considered quite successful but still less than optimal because there were several problems in it such as social media accounts that were no longer actively providing information, the quantity of mentoring policy implementers was still lacking, and there was no clear SOP in implementing the mentoring policy.